'I wasn't open to notes': S. Craig Zahler, Dragged Across Concrete (2018) and the 157-page screenplay. (1st April 2022) - Goodare, Lee
Drawn to its distinctive narrative style and length, in this article I examine writer-director S. Craig Zahler's third feature screenplay, Dragged Across Concrete. I focus on Zahler's authorship and creative writing, which flouts many screenwriting conventions. Zahler's screenplay, totalling 157 pages, is considerably longer than the recommended length of 90‐120 pages and it is examined and contextualized here via discussion of length, style, character, scenes, genre and dialogue. This analysis contributes to the formal study of the screenplay as a source text and aims to counter what Steven Price has termed the 'screenplay's near-invisibility in critical analysis'.